Career Guidance Services : Trait and Factor Career Theory Analysis - Elfi Churnia; Afdal Afdal; A Muri Yusuf (SCHOULID: Indonesian Journal of School Counseling, 2021)
The future challenge in life for students is self-preparation in choosing a career. Career choice is a determination in decision making as a process where a person makes his choice based on the abilities and qualifications of the students themselves, according to the characteristics of each major, interests, talents, and knowing plans for future career prospects. Trait and Factor can be interpreted as a directive-counseling or counselor- centered approach, having the basic view that human personality is a system of interdependent traits and factors. Trait and factor is a counseling style that emphasizes individual understanding through psychological testing and the application of that understanding  in solving  various  problems  faced,  especially  those  concerning  career choices. This article is a literature review that will explain career guidance and counseling services in terms of Trait and Factor Career Theory Analysis. Data in this study sourced by books and journals that are credible and reputable.